Penerapan Model Penta-Helix Dalam Pengembangan Potensi Pariwisata Di Kota Kupang - Alina Nujum; Marthen R. Pellokilla; Novi Theresia Kiak (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the role of Penta-Helix stakeholders in developing tourism potential in Kupang City. The method used is descriptive qualitative with a qualitative approach. The focus of this research is to observe and find out how the application of the Penta-Helix model in the development of tourism potential in Kupang City, using data collection techniques in the form of Interviews, Questionnaires and Documentation analyzed using Analytichal Hierarchy Process (AHP) analysis techniques. The results of this study show that the Penta-Helix Collaboration in developing the tourism potential of Kupang City has been implemented, but the results to advance tourism in Kupang City are still not optimal. This is due to the lack of awareness from the public and also coordination from the government in maintaining the safety and cleanliness of tourism places is lacking. Factors that become the scale of importance to the application of the Penta-Helix model of tourism in Kupang City based on the level of priority are aspects of government, private sector, society, media, and academia. For the government aspect, the indicator with the greatest weight is the construction of tourism facilities. For the private sector, the priority indicator is the improvement of service services. In the community aspect, the most priority indicator is the indicator of cleanliness of the tourist environment. For the media aspect, the priority indicator is tourism propotion. For the academic aspect, the indicator with the greatest weight is the development of research contribution facilities.